Sodium‐Containing Surface Film Formation on Planar Metal–Oxide Electrodes with Potential Application for Sodium‐Ion and Sodium–Oxygen Batteries. Issue 12 (18th October 2022) - Szabados, Lukas; Winkler, Daniel; Stock, David; Alexander, Thöny; Lörting, Thomas; Kunze-Liebhäuser, Julia; Portenkirchner, Engelbert
Abstract : Excellent, self‐improving sodiation rate capabilities in combination with high capacity retention upon galvanostatic charge/discharge cycling are found for oxygen‐deficient, carburized, and self‐organized titanium dioxide (TiO2− x ) nanotubes (NTs). The sodiation mechanism is attributed to the formation of an acicular surface film as the active storage material with sodium (Na) peroxide (Na2 O2 ) being the main component. Whether the proposed surface chemistry is unique for TiO2 NTs or serves as a common scheme for Na‐ion storage at metal oxide surfaces, in general, is not clear by now. Herein, three different materials, titanium(IV) oxide in the anatase and rutile phase and molybdenum(IV) oxide, are investigated in a planar electrode geometry toward their capability for Na‐ion storage. It is shown that all three materials under investigation demonstrate a significant progression of capacity increase upon cycling in combination with the formation of a Na‐oxide containing surface film. These "self‐improving" characteristics are found to significantly enhance the Na‐ion storage performance of the electrodes during long‐term galvanostatic cycling in a Na‐containing electrolyte. Abstract : The surface chemistry on metal oxides is investigated toward its capability for sodium‐ion storage. Excellent, self‐improving sodiation rate capabilities in combination with high‐capacity retention are related to surface film formation with inorganic compounds. Initially formed Na2 O2 reversibly converts to NaO2 upon desodiation.